Ethical Considerations in Research about Organizations: Compendium of Strategies - McGregor, Sue L. T. (Adam Mickiewicz University, Faculty of Philosophy, 2023)
This paper concerns ethical considerations when conducting research about the policies, procedures, practices, and culture of organizations and institutions rather than research with the humans owning, operating, employed at, volunteering for, benefiting from, or impacted by the organization. Ethical conventions for research with humans are well developed but less so for research about organizations. A pressing concern in the nascent literature is weighing protecting the public interest versus the organization’s interests when sensitive, controversial, or damning information about the latter emerges from the research. Given the absence of formally codified procedural ethics, organizational researchers are encouraged to constantly reexamine, debate, and address related ethical concerns. In that spirit, an inaugural compendium of ethical concerns and recommended strategies gleaned from the literature reviewed is shared, and a discussion of omissions from said literature is tendered to scaffold future conversations around this ethical aspect of organizational research.
Keywords: Research ethics; research about organizations and institutions; ethical concerns; procedural ethics; public interest; critical inquiries